3D printing of conductive organic polymers: challenges and opportunities towards dynamic and electrically responsive materials. (December 2022) - Martinelli, Angelo; Nitti, Andrea; Giannotta, Giorgio; Po, Riccardo; Pasini, Dario
Abstract: Since their discovery, conducting polymers have been the subject of longstanding attention for the development of electrically responsive devices. Modern methodologies of manufacturing, including additive manufacturing, are increasingly used in order to create three dimensional systems with controlled architectures. The merging of the two research areas is challenging, given the peculiar macromolecular and chemical characteristics of conductive polymers. We report here an overview about different 3D printing techniques, such as inkjet, extrusion, and light-based printing, for the production of electrically responsive functional materials and devitces for sensing, biosensing or actuative purposes. Recent examples in which the three main classes of conductive polymers, namely, polyaniline, poly(dioxy-3, 4-ethylenethiophene) and polypyrrole have been processed with additive manufacturing techniques are sequentially presented. Highlights: The merging of conducting polymers and 3D printing is discussed. The challenges in merging the two research areas are presented. Inkjet, extrusion, and light-based 3D printing techniques, are outlined.